Stock market linkage between China and ASEAN-6 countries: integration perspective - Zhang Jinghua,; Mori Kogid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper examines the integration process and time-varying characteristics of major stock markets in China and ASEAN-6 countries (Indonesia, Malaysia, the Philippines, Singapore, Thailand and Vietnam). Based on the DCC-GARCH model as related to the daily stock index return data of China and the ASEAN-6, from July 2000 to December 2022, our study showed that the dynamic correlation between the stock markets of China and the ASEAN-6 was significantly enhanced during the sample period. The level of stock market integration between China and Singapore, Malaysia, and Vietnam has increased significantly, and the correlation has become more stable. In addition, the integration process shows significant time-varying characteristics; the effect of major economic events, the development of domestic financial markets, and the opening process of capital markets have a significant impact on the integration process of regional stock markets. The study made recommendations to promote China-ASEAN financial cooperation and offers a reliable theoretical basis for investment portfolio decisions. This will assist policymakers in keeping up with economic trends and taking necessary policy measures and interventions in a timely and effective manner to control stock market risks, ensuring stable and healthy economic development.